2022
DOI: 10.1024/0301-1526/a000995
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of factors impacting lower limb major amputation rates in Hungary

Abstract: Summary: Background: Lower limb major amputations represent a substantial public health burden in Hungary, where previous research revealed markedly high rates with significant spatial variations. Therefore, we aimed to assess to what extent healthcare and socio-economic factors in the local environment explain the regional disparity. Patients and methods: In a retrospective cohort analysis, based on the healthcare administrative data of the Hungarian population, lower limb major amputations were identified fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…[83][84][85] Low nSES also increased the odds of having major lower-limb amputations. 34,86 Although iSES seems to play the more decisive role, a geostatistical model considering only the neighborhood revealed that nSES represented the predominant impact on amputation rate; the effect of healthcare service disparities was less influential, and 37% of the variability in amputation practice could be attributed to the living environment of amputees. 34 The socio-economic gradients in amputation rates may also exist when comparing different countries.…”
Section: Ses and Pad Carementioning
confidence: 99%
See 2 more Smart Citations
“…[83][84][85] Low nSES also increased the odds of having major lower-limb amputations. 34,86 Although iSES seems to play the more decisive role, a geostatistical model considering only the neighborhood revealed that nSES represented the predominant impact on amputation rate; the effect of healthcare service disparities was less influential, and 37% of the variability in amputation practice could be attributed to the living environment of amputees. 34 The socio-economic gradients in amputation rates may also exist when comparing different countries.…”
Section: Ses and Pad Carementioning
confidence: 99%
“…34,86 Although iSES seems to play the more decisive role, a geostatistical model considering only the neighborhood revealed that nSES represented the predominant impact on amputation rate; the effect of healthcare service disparities was less influential, and 37% of the variability in amputation practice could be attributed to the living environment of amputees. 34 The socio-economic gradients in amputation rates may also exist when comparing different countries. A striking difference in amputation rates across Europe is an example of the East/West divide in health 87 that may be partly accounted for by the complex disparities found in socio-economic characteristics of Western European and Central and Eastern European countries.…”
Section: Ses and Pad Carementioning
confidence: 99%
See 1 more Smart Citation
“…Statisz tikai elemzéseink szerint egy adott járás incidenciaértéke lokális, szomszédsági, megyei, az eddigiekben részleteiben nem feltárt tényezôkre vezethetô vissza. Legújabb komplex térelemzésünk szerint a járásokra vonatkoztatott amputációs aktivitás még csak nem is a járóbeteg-ellátás (háziorvosi, érsebészeti, angiológiai) strukturális mutatóitól, vagy az adott járásra vonatkoztatott revascularisatiós aktivitásától függ, hanem sokkal inkább az egészségügyi ellátáshoz csak közvetetten kapcsolható, annál sokkal szélesebb értelmû szocioökonómiai háttértôl (16). Mindez nagyon komplex tényezôk együtthatását sejteti, ami nem meglepô, tekintettel az amputációk distalis ki -meneteli indikátor természetére.…”
Section: Az Alsó Végtagok Verôérbetegséggel éS Cukorbetegséggel Kapcs...unclassified